FAMILY BASED SOCIO-ECONOMIC FACTORS THAT AFFECT STUDENTS’ ACADEMIC PERFORMANCE IN PUBLIC SECONDARY SCHOOLS IN RONGO SUBCOUNTY, MIGORI COUNTY, KENYA - Rose A., Adhanja,; Peter. O., Dr. Nyakan,; John M. O., Dr. Yambo, (IJRDO - Journal of Business Management, 2016)
Quite a number of factors have been found to influence students’ achievement. Secondary schools in Rongo sub-county have been performing dismally as compared to other Sub-counties in the region. The purpose of the study was to determine the contributions of socio-economic factors on academic performance in secondary schools in Rongo sub-County, Migori County. Objective of the study was to identify family based socio-economic factors that affect students’ academic performance in public Secondary schools in Rongo sub-County, Migori County, Kenya. The study used descriptive survey and correlational research designs. The study was also guided by a conceptual framework. The targeted population was 45 head teachers, 547 TSC secondary school teachers, 14,523 secondary students, 5 ZQASOs. The researcher used saturated sampling technique to select 40 head teachers and 5 ZQASOs, simple random sampling was used to select 165 TSC class teachers and purposive sampling was employed in selecting 2250 students. The instruments of data collection were questionnaires, in-depth interview, observation and document analysis. Reliability of the instruments was addressed through piloting in 5 schools and reliability coefficients were obtained by subjecting the instruments to a Split-half Technique and Spearman “Brown Prophesy formula” .To ensure face and content validity of the research instruments, 2 experts in the department of Educational Administration, Planning and Economics were requested to scrutinize the research instruments so as to validate them. Data was analyzed using both qualitative and quantitative methods. Findings and conclusions of the study were generated from the analysis. The study found out that Parental level of education significantly affects academic performance 4.6(92%). The study concluded that Parents and guardians should be more enthusiastic about their children’s academic performance. The researcher therefore recommended that home environment should be made conducive for learning to supplement what the school provides.